2010
DOI: 10.1371/journal.pone.0009526
|View full text |Cite
|
Sign up to set email alerts
|

The PPARβ/δAgonist GW0742 Relaxes Pulmonary Vessels and Limits Right Heart Hypertrophy in Rats with Hypoxia-Induced Pulmonary Hypertension

Abstract: BackgroundPulmonary vascular diseases are increasingly recognised as important clinical conditions. Pulmonary hypertension associated with a range of aetiologies is difficult to treat and associated with progressive morbidity and mortality. Current therapies for pulmonary hypertension include phosphodiesterase type 5 inhibitors, endothelin receptor antagonists, or prostacyclin mimetics. However, none of these provide a cure and the clinical benefits of these drugs individually decline over time. There is, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 31 publications
5
40
0
Order By: Relevance
“…The reasons for this discrepancy are not clear, but such variability is generally attributed to differences in the diabetogen used, the sex, species, and/or strain of the animals, the animal breeder, the duration of the hyperglycemia, and/or the blood pressure-measuring techniques and the experimental conditions. In the present study SBP was similar in STZ-diabetic rats than in the age-matched controls, and was unaltered by PPARb/d activation, an observation supported by previous reports showing that GW0742 treatment does not influence SBP in normotensive rats [42], but reduced blood pressure in hypertensive animals [23]. Pulmonary artery endothelial dysfunction, elevated pulmonary arterial pressure, and the subsequent right ventricular hypertrophy have been found in rats treated with STZ [33,43].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reasons for this discrepancy are not clear, but such variability is generally attributed to differences in the diabetogen used, the sex, species, and/or strain of the animals, the animal breeder, the duration of the hyperglycemia, and/or the blood pressure-measuring techniques and the experimental conditions. In the present study SBP was similar in STZ-diabetic rats than in the age-matched controls, and was unaltered by PPARb/d activation, an observation supported by previous reports showing that GW0742 treatment does not influence SBP in normotensive rats [42], but reduced blood pressure in hypertensive animals [23]. Pulmonary artery endothelial dysfunction, elevated pulmonary arterial pressure, and the subsequent right ventricular hypertrophy have been found in rats treated with STZ [33,43].…”
Section: Discussionsupporting
confidence: 91%
“…In the present study we also found right ventricular hypertrophy in diabetic rats, which was reduced by chronic GW0742 treatment, suggestive of improved pulmonary artery function. This is consistent with the therapeutic benefit of GW0742 in pulmonary arterial hypertension in a rat model of chronic hypoxia [42].…”
Section: Discussionsupporting
confidence: 86%
“…9 PPAR␤ agonists also induce vasodilator effects in isolated aortas and mesenteric and pulmonary arteries. 10,11 Furthermore, a PPAR␤ agonist reduced the right heart hypertrophy and right ventricular systolic pressure in an experimental model of pulmonary arterial hypertension induced by chronic hypoxia. 11 We hypothesized that the PPAR␤ agonist GW0742 would reduce blood pressure, improving vascular inflammation and endothelial function in the spontaneously hypertensive rat (SHR).…”
mentioning
confidence: 99%
“…3,4 We have recently shown, using a hypoxia model of pulmonary hypertension in rats, that GW0742, a ligand for peroxisome proliferator-activated receptor (PPAR) β/δ, 5 reduces right heart hypertrophy without influencing pulmonary vascular remodeling. 6 This was a somewhat unexpected finding, since we and others found GW0742 to relax pulmonary vessels 6 or vascular cells 7 and to inhibit lung cell proliferation in vitro. 8 Despite this, however, the in vivo data suggested that GW0742 might have a direct protective action on the right heart in this model.…”
Section: Introductionmentioning
confidence: 80%
“…8 Despite this, however, the in vivo data suggested that GW0742 might have a direct protective action on the right heart in this model. 6 PPARβ/δ is expressed in the heart, where it regulates metabolism 9 and protects against ischemia reperfusion injury. 10,11 In addition, a recent study by Liu et al 12 used a transverse aorta constriction model and showed that left ventricular dilation, fibrosis, and mitochondrial abnormalities were reduced in transgenic mice in which constitutively active PPARβ/δ was expressed.…”
Section: Introductionmentioning
confidence: 99%